En ensom norsk grav i Poznań - Lange, Tadeusz Wojciech (Folia Scandinavica Posnaniensia, 2015)
The article is an account of the life and death of Halldor Espelid, a young Norwegian RAF pilot born in Bergen, trained at “Little Norway” in Canada, shot down over occupied France, put in the POW camp for airmen in Sagan (now Żagań in Poland), arrested near Flensburg while taking part in the so-called Great Escape, and murdered at the age of 24 by the Kiel Gestapo. His body was cremated, his ashes buried at Sagan and later moved to the Old Garrison Cemetery in Poznań, Poland, together with the remains of 47 other participants of the famous Great Escape murdered at Hitler’s personal order.